FAKTOR – FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI BEI - Septiani, Dinda Aulia; Bangun, Nurnainun (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The study aims to show the impact of growth Opportunities, investment decisions and capital structure on Firm value in manufacturing companies listed on the Indonesia Stock Exchange Industrial (IDX) in the period 2019-2021. The method used in this study is purposive sampling with a total data collected of 27 companies that met the criteria. Data processing techniques used descriptive analysis using E-views 10th version and Microsoft Excel 2010 edition. Results of this study has concluded that the variables growth opportunity had a significant effect on firm value, which indicated that changes in score has occurred within the company influenced. by the opportunity the company has to develop. The variable Investment decisions and capital structure have no significant effect on firm value which means that changes in firm value score are not affected by the variable capital structure and investment decisions.